Indonesian elementary students' achievement in learning English speaking through viewing Hello Talk: The effectiveness - Fauzi, Ikhwan; Daulay, Sholihatul Hamidah; Dewi, Utami; Irham, Novia Robeitah (Universitas Negeri Yogyakarta, 2024)
Discussions on the subject of Mobile Assisted Language Learning (MALL) are made more interesting by this study. In particular, the work concentrated on Hello Talk's smartphone app, which promotes language learning and acquisition through communication with native speakers and other language learners. This study aims to know the effectiveness of viewing the Hello Talk application for Indonesian elementary students' speaking learning. A mixed method (qualitative and quantitative design) methodology was utilized in this study. Participants in this study were 10 students from sixth-grade elementary schools. The respondents were selected on purpose based on their own experiences of viewing the Hello Talk application during the process of learning English. Questionnaires and interviews were used as the research instruments in this study. The questions on the questionnaire were focused on students' motivation in viewing the Hello Talk app, their expectations, effectiveness, and confidence level after viewing the app. The result shows that more than 50% of the participants were motivated to view the Hello Talk application to improve their English language proficiency. About 35% of participants expected that viewing the Hello Talk application can improve students speaking ability, and the effectiveness of viewing Hello Talk is 50%, which means that half of the participants argue that this application is highly effective. The last percentage is about the students' confidence after viewing this app, it is about 38% in level 5 of 5.